Field guide to case study research in business-to-business marketing and purchasing - Woodside, Arch G.; Pattinson, Hugh; Marshall, Roger (Emerald, 2014)
This accessible field guide covers practical steps and contributes to behavioral theory by reporting intricate details on the strategies implemented by business-to-business firms within an inter-firm context. The coverage is deep, broad, and unique--the authors of the 14 papers all adopt the understanding that researchers need direct viewing--'eyes-on-the-context'--that goes beyond the use of paper-and-pencil 5-point and 7-point survey items to achieve accurate descriptions of how decisions are made and progress achieved. Following the customary introductory chapter, the titles of the 13 remaining chapters promise the reader new insights and tools to apply when studying B2B contexts. This new volume in the Advances in business marketing and purchasing series is a must for B2B scholars and executives.
Keywords: Business & Economics -- Marketing -- Industrial.; Sales & marketing.; Industrial marketing -- Research.; Purchasing -- Research.; Marketing research.; elektronické knihy; electronic books